Effect of heat on psycho-physiological responses during a self-paced cycling time trial - Pirlot, T.; Baron, B.; Ravier, G.; Groslambert, A. (Journal of Science and Cycling, 2025)
As global temperatures rise and competitions increasingly take place in hot environments, understanding the impact of heat on performance is critical (Hunter et al., 2002). Thermal stress induces cardiovascular strain, alters brain activity, and modifies perceptual and motivational responses, affecting pacing and endurance (Périard et al., 2015). While studies have reported changes in heart rate (Girard & Racinais, 2014), muscle oxygenation, and cognitive function under heat (Nybo & Nielsen, 2001), few have focused on self-paced exercise. This study examines how heat affects performance, perceptual responses, motivation, and neural efficiency in trained cyclists during a simulated self-paced time trial.